Diseño de un sistema de mejora continua mediante la filosofía del mantenimiento productivo total (TPM) en la empresa INDUACERO CÍA. LTDA. - Collaguazo Malliquinga, Stalyn Mauricio (2018)
The study of the improvement of the global efficiency of the machines and equipment in the production lines in the company INDUACERO Cía. Ltda., Based on the development and design of a continuous improvement system TPM (Total Productive Maintenance), aims to improve the availability of machines and equipment thus reducing unproductive times and help the organization to fulfill the following achievements: without wastage, accidents, defects and breakdowns. An overall efficiency analysis of the machines and equipment was carried out in all the production lines of the company in order to identify the potential factors that affect the OEE index. The company presented an average of 66% overall equipment efficiency, that is in a regular index. The main factor is the low availability of machines and equipment, which is 78 %, it occurs by factors such as the assignment of tasks from production, order to the maintenance technician and the small technicians. In the maintenance department to perform preventive tasks in machines and equipment, this causes an average of unproductive times of 28.25 hours per month in the production. It is to consider that the approximate cost per hour of production in the company is of $ 198,00, and then these stops cause economic losses to INDUACERO Co. Ltda. Of $ 5.593,50 monthly. The development of the TPM continuous improvement system in the company INDUACERO Co. Ltda., Has the purpose of demonstrating the feasibility that the implementation of the project would have both technically increasing the overall efficiency of the equipment by 11%. The proposal has a significant impact benefiting all personnel within the company considering the administrative and operational staff.